Transformation and differentiation of Henstock-Wiener integrals - Varayu Boonpogkrong; de Lara-Tuprio, Elvira Pederes (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper, transformation and differentiation of Henstock-Wiener integrals are discussed. The approach is by Riemann sums. The idea is more transparent than that of classical Wiener integral.